Implementation of Field Oriented Control on Permanent Magnet Synchronous Motor - Dave, Smit; S Shah, Siddhant; Shetty, Divya (International Journal of Engineering and Technology, 2018)
This paper proposes the control of a Permanent Magnet Synchronous Motor through Field Oriented Control algorithm coded on an FPGA controller which can be used in electric vehicles. Field Oriented Control method was chosen as it was found to be useful for electric vehicles for speed control. The paper details the implementation of Field Oriented Control on PMSM using MATLAB and Xilinx. The Hardware setup is 2 level IGBT inverter, FPGA controller and Permanent Magnet Synchronous Motor. Results obtained from practical implementation show that Field Oriented Control was successfully implemented. The speed control of PMSM was achieved and also the objectives of simulating the above scenario and observing power losses was accomplished. The FOC simulation of MATLAB shows system behaving similarly to the set point reference inputs given by the user.Â Â